Respons Produksi Dua Varietas Bawang Merah (Allium ascalonicum L.) Terhadap Aplikasi Beberapa Jenis Pupuk Hijau - Nur Laila; Lisa Mawarni; Yaya Hasanah (Jurnal Agroekoteknologi, 2015)
Green manure is the fresh form of crop forage material added in the soil to increase the growth andproduction of shallot. This research was proposed to find out response of two varieties of shallot ingrowth and production on green manures. Research had been conducted at experimental field of theAgricultural Faculty USU in May to August 2014, using factorial randomized block design withtwo factors, two varieties of shallot (Medan and Bima) and green manures (control, Tithoniadiversifolia, Mucuna bracteata, Azolla pinnata). The results showed that treatment of varietiessignificant affected in harvesting age, bulb number per sample, bulb fresh weight per sample, andbulb dry weight per sample. The treatment of green manures significant affected increasing bulbfresh weight per sample and bulb dry weight per sample. The interaction of both parameterssignificant affected bulb numbers per sample of shallot. The best result were showed by variety ofBima and green manure of Mucuna bracteata.Keywords : shallot, green manure, variety